(untitled) (Revista Electrónica REDINE, 2017)
This is a mixed approach investigation. In this sense, the researcher uses both qualitative and quantitative resources to obtain and analyze the data. In this regard, it was made an observation and then a qualitive interpretation of the university student’s behavior of the current era. Besides, it was objectively reviewed the virtual classroom of English II located in the Distance Education System of the Centroccidental University Lisandro Alvarado known as SEDUCLA, specifically of the Deanery of Science and Technology known as DCyT, on the career of Production Engineering . The purpose of this research was focused on recognizing the importance of adopting the hypermodern vision in virtual learning environments (VLE) according to the characteristics of the current university student. In this sense, it were made some comparisons among the characteristics of this historical time, the current university student, and the observed virtual classroom. The qualitative nature of this research allowed associating the hypermodern characteristics of the time with what the researcher (teacher) subjectively considers as the behavior style of the students (technology native) users of the VLE. Finally, it was concluded that current education is different from that of the past, especially in terms of technology usage and its impact on teachers, students, resources, strategies and contexts. Also, the VLE must be presented to students attending to the hypermodern characteristics of the current time and in accordance with the statistical registers thrown by the observed VLE itself.